THE SECOND WORLD WAR IN AMERICAN LITERATURE (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Abstract: Post-World War II American literature was marked by a number of significant developments and changes. The war had a profound impact on American society and culture, and this was reflected in the literature of the time. Post-World War II American literature is characterized by a variety of themes and styles. One of the most significant developments of this period was the emergence of the Beat Generation, a group of writers who rejected mainstream American culture and sought to explore new forms of expression.Post-World War II American literature was also marked by a growing sense of disillusionment with the American Dream, as writers began to question the values and ideals of mainstream society.